Analysis of WIUM Online Education Management System User Satisfaction Using PIECES Framework - Bangun, Winda Ebina Br; Sihotang, Jay Idoan (Universitas Muhammadiyah Magelang, 2023)
WIOEM is a web and android application designed to quickly share information with users and help solve problems at the Salemba Adventist College. This information system is used by users for various purposes that are able to support the performance of teachers and parents in improving services to students. The various functions in this information system will affect user satisfaction or dissatisfaction with the system. So that there is a need for improvement and development of the system in the future. WIOEM information system analysis was carried out to determine the advantages and disadvantages that exist in the system based on the PIECES method. The purpose of this research is to get an overall picture of system performance, information, level of economic value, security, efficiency, and system services. From each aspect that is analyzed will be used as a recommendation for improvement of the WIOEM information system. The method used in this research is descriptive quantitative. The data collection technique uses a questionnaire distributed through the Google Forms platform. The results of this study indicate that the WIOEM system is in the good category, with an average total satisfaction level of 4.18. With each Performance indicator achieving a value of (4.31), Information (4.23), Economic (4.04), Control (4.11), Efficiency (4.25) and Service achieving a value of (4.17).